2014
DOI: 10.1080/14742837.2014.945158
|View full text |Cite
|
Sign up to set email alerts
|

Managing Democracy in Social Movement Organizations

Abstract: Leaders are crucial to social movement mobilization and maintenance. They often experience conflict between a value for inclusive engagement and a sense that they are moving efficiently toward their organizations' goals. This study draws on a multisite ethnography to suggest two mechanisms through which leaders may resolve this conflict: staging (manipulating organizational procedures) and scripting (using language to reinforce these procedures). Resolving tension in this way often leaves the leader in control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Writing specifically about prefigurative movements, Maeckelbergh argues, ‘horizontality is believed by many movement actors to be the best way to create equality … horizontality means actively creating practices that continuously challenge inequalities – both structural and inter-personal’ (Maeckelbergh, 2011, p. 10). Yet as mentioned earlier, scholars studying contemporary prefigurative movements have shown that these movements are failing to tackle existing inequalities and patterns of exclusion (Athanasiou, 2014; Choi-Fitzpatrick, 2015; Gamez Fuentes, 2015). Given our focus on how prefigurative movements not only acknowledge but also tackle the reproduction of inequalities in group spaces and our process-centred approach (Choo & Ferree, 2010), we now turn to examine how activists translate intersectional prefiguration into practice.…”
Section: Developing a Culture Of Intersectional Organisingmentioning
confidence: 98%
See 2 more Smart Citations
“…Writing specifically about prefigurative movements, Maeckelbergh argues, ‘horizontality is believed by many movement actors to be the best way to create equality … horizontality means actively creating practices that continuously challenge inequalities – both structural and inter-personal’ (Maeckelbergh, 2011, p. 10). Yet as mentioned earlier, scholars studying contemporary prefigurative movements have shown that these movements are failing to tackle existing inequalities and patterns of exclusion (Athanasiou, 2014; Choi-Fitzpatrick, 2015; Gamez Fuentes, 2015). Given our focus on how prefigurative movements not only acknowledge but also tackle the reproduction of inequalities in group spaces and our process-centred approach (Choo & Ferree, 2010), we now turn to examine how activists translate intersectional prefiguration into practice.…”
Section: Developing a Culture Of Intersectional Organisingmentioning
confidence: 98%
“…While accepting that point, our objective in this article is to examine how, in selfidentified prefigurative groups, where there is an explicit emphasis on enacting a different kind of politics and practice (i.e., non-hierarchical, utopian), both within the group and beyond, structural inequalities persist and how these are acknowledged and addressed. This is important as studies of recent prefigurative movements demonstrate, despite claims of inclusivity and the adoption of horizontal procedures and structures, such movements continue to reproduce inequalities and exclusionary practices found in society, as a result of which the voices and demands of women, as well as racial and ethnic minorities, become marginalised in organisational spaces limiting their ability to shape agendas of action (Athanasiou, 2014;Campbell, 2011;Choi-Fitzpatrick, 2015;Gamez Fuentes, 2015;Potuouglu-Cook, 2015). For instance, despite the claims that the Occupy movement was structured to 'give voice' to underrepresented people (Vallee, 2017), this was not necessarily achieved in practice.…”
Section: Intersectional Prefigurationmentioning
confidence: 99%
See 1 more Smart Citation
“…Los estudiosos del movimiento social recién empezaron a mostrar más interés en las organizaciones de los movimientos sociales. Los principales temas de investigación han sido las estructuras internas y los procesos de decisiones (Della Porta et al, 2009;Leach, 2009;Kreiss, 2014;Polletta, 2002;Maeckelbergh, 2012;Choi-Fitzpatrick, 2014;Polletta, 2005), liderazgo y jerarquía (Milam y Heath, 2014;Sutherland et al, 2013;Spicer y Böhm, 2007;Briscoe y Safford, 2008;Western, 2014), conflictos (Laamanen y den Hond, 2015; Maeckelbergh, 2012), y las rutinas cotidianas (Glass, 2010;Tilly, 1995). Las contribuciones relacionadas con la teoría organizacional suelen referirse al concepto de organizaciones prefigurativas.…”
Section: Las Oms En La Teoría Organizacionalunclassified
“…Two exceptions are Choi-Fitzpatrick, who argues that despite the "appearance of inclusive engagement" the voices of African American and Latino participants were "often not heard" in recent social justice and democracy movements in the US, while the "Anglo participants" dominated the programme and conversations; and Martinez Palacios, who finds that the participation of women was restricted in practice in the Spanish 15M movement. 40 Likewise, we urge a more critical examination which examines the intersectionality within movements. Movements often claim to be inclusive and yet, upon investigation we discovered that age, class, gender, race, and religion can affect organizing and mobilizing within movements.…”
Section: Experimentation and Effectivenessmentioning
confidence: 99%